Relativistic convergent close-coupling calculation of spin asymmetries for electron–indium scattering - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (Institute of Physics Publishing Ltd., 2012)
The measurements of Bartsch et al (1992 J. Phys. B: At. Mol. Opt. Phys. 25 1511) of the left–right spin asymmetry for elastic and inelastic scattering of polarized electrons from unpolarized indium atoms are compared with corresponding relativistic convergent close-coupling (RCCC) calculations over the full range of energies (1–14 eV) and 5p 2Po1/2 → 5p 2Po1/2, 5p 2Po1/2 → 5p 2Po3/2, 5p 2Po1/2 → 6s 2S1/2 and 5p 2Po3/2 → 6s 2S1/2 transitions. There is very good agreement between theory and experiment for elastic scattering spin asymmetries. Some discrepancies still exist between the RCCC results and experiment for excited state spin asymmetries.